Spotkanie w pół drogi. O Marii Konopnickiej i Zofii Nałkowskiej (z Katherine Mansfield w tle) - Magnone, Lena (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
The author discusses the relationships between Maria Konopnicka’s and Zofia Nałkowska’s works, the two writers who are usually contrasted. The main body of the article is a comparison between Konopnicka’s prison reports, written for the press in the 1880s, and the 1931 short-story collection by Nałkowska, Ściany świata [The Walls of the World]. For Nałkowska, the author of Za kratą [Behind the Bars], the documen tary form of a press report was an opening point, and her experiments with prose were crowned twenty years later with the intimate, modernist short-story collection called Na normandzkim brzegu [On the Shores of Normandy]. Nałkowska goes in the opposite direction: she gradually turns away not only the from the egocentrism of her modernist novels, but also from the over-structured language and style of her Young Poland phase. She was going in the direction of the pure, precise narrative of Medaliony [The Medallions], for which Ściany świata are a kind of prefiguration. The author of the article proposes to conclude that both writers met halfway. The convergences between short-story writing by Konopnicka and some works by Nałkowska (Charaktery, Dom nad łąkami) have been underscored by the comparison with Katherine Mansfield, a comparison which seems obvious for both Polish writers. Both Konopnicka and Nałkowska could be described as “the Polish Katherine Mansfield”, and the similarity is the best indication of the relationship between the two writers.